منهج المدرسة العقلية الحديثة في القصة القرآنية - خليفة خليفة (University Of Eloued جامعة الوادي, 2024)
تعتبر "المدرسة العقلية الحديثة"، من أهم المدارس التجديدية التي عرفتها الأمة الإسلامية، وليس يخفى أن هذه المدرسة قد اتخذت القرآن الكريم وسيلة وغاية؛ وسيلة تستعين بها المدرسة لإصلاح حال الأمة الإسلامية، وغاية تريد من وراء عملية الإصلاح إرجاع الناس إلى هدي هذا الكتاب الكريم. وبما أن القصص جزء معتبر من القرآن فلا بد أن يحظى بعناية خاصة من قبل المدرسة العقلية الحديثة. وهذا الذي حاولت هذه الدراسة بيانه وعرضه، وذلك بتقسيم الموضوع إلى ثلاثة أبواب الباب الأول: وهو على ثلاثة فصول؛ الفصل الأول للتطرق إلى مفهوم القصة القرآنية وأهم خصائصها. وفي الفصل الثاني: ترجمتُ فيه للأستاذ محمد رشيد رضا، والفصل الثالث: ترجمتُ فيه أعلام المدرسة العقلية الحديثة وعرضت جهودهم والانتقادات عليهم. والباب الثاني كان على ثلاثة فصول: الفصل الأول: بينتُ فيه أهم الركائز التي يقوم عليها منهج المدرسة العقلية في القصص الفصل الثاني: بيّنتُ فيه أساليب القرآن في عرض القصص وفق منظور المدرسة العقلية الحديثة والفصل الثالث: لسرد أغراض القصص القرآني. الباب الثالث: وهو على فصلين: فالفصل الأول: ركّزت فيه على مقومات منهجه "رحمه الله" ،وهي خمسة؛ التأويل، والتمثيل، والتكرار، والإسرائيليات، والضابط السنني في القصص. والفصل الثاني: جعلته لأغراض القصص عنده . Abstracts The “Modern Intellectual School” is considered one of the most important schools of renewal known to the Islamic nation, and it is no secret that this school has taken the Holy Qur’an as a means and an end. A means used by the school to reform the condition of the Islamic nation,and an aim behind the reform process is to return people to the guidanceof this noble book. Since stories are an important part of the Qur’an, they must be given special attention by the modern rational school. This is what this study attempted to explain and present by dividing the topic into three sections Chapter One: It has three chapters: Chapter One: To address the concept of the Qur’anic story and its most important characteristics. In the second chapter: I translated it for Professor Muhammad Rashid Reda, and the third chapter: I translated the notables of the modern rational school and presented their efforts and criticisms. The second chapter was divided into three chapters: the first chapter: in which I explained the most important pillars upon which the rationalistic school’s approach to stories is based, the second chapter: in which I explained the methods of the Qur’an in presenting stories according to the perspective of the modern rationalistic school, and the third chapter: to narrate the purposes of the Qur’anic stories . Chapter Three: It has two chapters: The first chapter: I focused on the components of his approach, which are five; Interpretation, representation, repetition, Israelis, and the Sunni rule in stories. The second chapter: I made it for the purposes of his stories.
محمد رشيد رضا أنموذجا
أطروحة
Keywords: القصة القرآنية; المدرسة العقلية الحديثة; محمد رشيد رضا; الإصلاح الديني; The Qur’anic story; the modern rational school; Muhammad Rashid Reda; religious reform